Investor Reaction to Consumer Sentiment: The Case of Manufacturing Firms in Indonesia - Soni Hakim (Universitas Sebelas Maret, 2016)
This study aims to determine the influence of industrial workers concentration on the consumer confidence index and the influence of consumer confidence index on the capital market, especially stock issuers from manufacturing industry sector. The data used in this research is secondary data with the sample of consumer confidence index taken from Jakarta and Surabaya as well as 47 manufacturing industry stock issuers listed in Indonesia Stock Exchange. This research isconducted by using Granger Causality method. The results generally show that there is no influence found for regional consumer confidence index with large manufacturing industry and regional consumer confidence index with relatively small manufacturing industry towards the national consumer confidence index. Research has also managed to find a significant influence of consumer confidence index on the price of stocks issued by several manufacturing companies.